Hubungan Tingkat Pengetahuan, Personal Hygiene dan Lingkungan Rumah terhadap Kejadian Tinea pada Nelayan di Kecamatan Kalianda - Dwimas Andi Prabowo; Merry Tyas Anggraini; Kanti Ratnaningrum (Jurnal Anestesi, 2025)
Tinea is a dermatophyte infection identified in 52% of incidences in the archipelago, with the highest prevalence of tinea inguinalis and tinea corporalis. Coastal workers, especially fishermen who are active in the aquatic environment, have a high predisposition to tinea due to a lifestyle that is negligent to hygiene, high humidity levels, tropical ambient temperatures, the use of damp clothing, accumulation of sweat, and dermal friction that accelerates the proliferation of mycoses. This study aims to evaluate the correlation between the level of cognition, personal hygiene, and domicile conditions to the incidence of tinea among fishermen in Kalianda sub-district. This analytic observational study with a cross-sectional approach involved 44 fishermen respondents who were taken through a simple random method. Data collection included questionnaire survey, clinical examination, and supporting investigation, with statistical analysis using chi-square test. Findings showed that limited cognition increased the probability of tinea by 5-fold, while poor personal sanitation increased the probability by 3-fold. Furthermore, inadequate housing conditions increased the risk by 2-fold. Therefore, the level of knowledge, personal hygiene, as well as the quality of the living environment significantly contributed to the prevalence of tinea in fishermen.